2019
DOI: 10.5897/ajb2019.16826
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of the performance of a stay-green sorghum (Sorghum bicolor (L) Moench) introgression line developed by marker-assisted selection and its parental lines

Abstract: A glasshouse experiment was conducted to compare the performance of a stay-green QTL introgression line (RSG 03123) and its parental lines (B35, a stay-green and R16, a high yielding cultivar with rapid senescence) after flowering, when water-limited (WL) or well-watered (WW). Flowering time and plant height were similar in RSG 03123 and the recurrent parent, R16. Under WW conditions, retention of green leaf area (GLA) and chlorophyll was similar in RSG 03123 and R16, whereas under WL conditions RSG 03123 reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…SG has been extensively used to improve tolerance to drought and heat in sorghum (Sanchez et al, 2002;Vadez et al, 2013) and maize (Wang et al, 2012;Cerrudo et al, 2017). There is ongoing research at the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) to transfer QTLs conditioning SG into genetically diverse, tropically adapted elite sorghum varieties for drought tolerance through marker-assisted backcrossing (MABC) (Isaac et al, 2019). Yang et al (2017) studied SG QTLs in maize using a heterogeneous inbred family approach and found that the SG-associated parameters were significantly correlated with crop yield.…”
Section: Stay Green Traits For Striga Resistance In Maizementioning
confidence: 99%
“…SG has been extensively used to improve tolerance to drought and heat in sorghum (Sanchez et al, 2002;Vadez et al, 2013) and maize (Wang et al, 2012;Cerrudo et al, 2017). There is ongoing research at the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) to transfer QTLs conditioning SG into genetically diverse, tropically adapted elite sorghum varieties for drought tolerance through marker-assisted backcrossing (MABC) (Isaac et al, 2019). Yang et al (2017) studied SG QTLs in maize using a heterogeneous inbred family approach and found that the SG-associated parameters were significantly correlated with crop yield.…”
Section: Stay Green Traits For Striga Resistance In Maizementioning
confidence: 99%